Patient Preferences For Specialty Pharmacy Services: A Stated Preference Discrete-Choice Experiment in China - Hu, Qinyuan; Hu, Haiyao; Hu, Ming; Yang, Yumei; Wu, Zhiang; Zhou, Naitong (Frontiers in Public Health, 2020)
Objectives: To survey, analyze, and ascertain the preferences for specialty pharmacy services among patients requiring complex care and to provide evidence to support specialty pharmacy service decision-making in China. Methods: To identify essential service attributes and levels, a review of the literature, discussions with specialty pharmacy managers and a pilot questionnaire were conducted. A D-efficient fractional factorial design was used to generate the discrete-choice experiment (DCE) questionnaire. A face-to-face survey of patients with chronic illness and their families or friends was conducted at three specialty pharmacies in Chengdu and Qingdao, China. A mixed logit model was used for estimation. Results: Six relevant attributes were identified and incorporated into the DCE questionnaire. A total of 417 participants completed the survey (mean age 43 years, 45.1% males), and 32.1% had lung cancer. The conditional relative importance showed that the most critical attribute was “frequency of telephone follow-up to monitor adverse drug reactions (ADRs), “followed by “mode of drug delivery,” “provider of medication guidance services,” and “availability of medical insurance consultation”; the least important attribute was “business hours.” A 1 min increase in time spent led to a 0.73% decrease in the probability that a service profile would be chosen. Negative preferences were noted for ADR monitoring by telephone follow-up once a year (β = −0.23, p < 0.001) and business hours [8:30–20:00 (Monday to Friday), 8:30–17:30 (weekend)] (β = −0.12, p < 0.001). Compared with women, men had a higher preference for service monitoring ADRs once every 3 months. Conclusions: Preference measurements showed that “frequency of telephone follow-up to monitor ADRs” had the most critical impact on decisions, followed by “mode of drug delivery.” Specialty pharmacies in China need to take these findings into account to improve their design to increase uptake and patient loyalty.